Grammatical Construction of Verb-Particle "off" in English - Astri Arni Murdasari Dewi (NOTION: Journal of Linguistics, Literature, and Culture, 2019)
This research investigates language phenomenon of verb-particle construction with particle "off" in English. This attempts to describe grammatical construction of verb-particle off. This research was conducted by descriptive-qualitative research method. The implementation of this method was through a number of stage: data gathering, analyzing data, and presenting the result of the data analysis. The stage of analyzing the data was performed by using distributional and identification method with a number of techniques. This study found that verb-particle construction can be distinguished from verb-preposition construction by implementing some of construction alternations, which are (1) noun phrase as object can be put in between the verb and the particle or after the particle; (2) coordinate noun phrase as object with the phrasal verb; (3) moving noun phrase to the left by itself is acceptable if without particle, that this indicate the noun phrase is a unit, but moving the particle and the noun phrase is not acceptable, since they do not form a phrase. The argument structure of verb-particle with off consists of intransitive, transitive, and ditransitive. The argument's role of verb-particle off can take action as agent, patient, and potential agent.